MACHINING PARAMETERS OPTIMIZATION FOR TRIMMING OPERATION IN A MILLING MACHINE USING TWO LEVEL FACTORIAL DESIGN - Minhat, Mohamad; Kasim, Mohd Shahir (2014)
Trimming process using Solid Carbide, 4 flute endmill of 8mm diameter tool on stacks of multidirectional CFRP/Al-2024 in a CNC Milling machine was experimentally investigated. The machining parameters considered were Spindle speed (N), Feed rate (fr) and Depth of cut (dc). The aims were to analyze the influence factors and the interaction of these parameters with respect to surface quality produced. A Two Level Factorial Design method was used to plan systematic experiments. The influence factors and the interaction between these parameters are analyzed and the optimum machining parameters for minimizing the surface roughness is determined. The analysis of variance (ANOVA) shows that Depth of cut (dc) and Feed rate (fr) are the most significant parameters to the overall performance of surface quality. Surface roughness of CFRP is found to be 1.778 μm and AL2024 is found to be 0.983 μm at the setting of N = 1860 rpm, fr = 620 mm/min and dc = 0.12 mm respectively. The validation test shows deviation of predicted value surface roughness is 7.87% for CFRP and 6.61 % for AL2024.